Reconstruction Interfaith Marriage Law in Indonesia: Relevance of Sociology Knowledge and Maqasid Sharia - Ibnudin, Ibnudin; Sugianto, Sugianto; Kholiq, Achmad; Aziz, Abdul; Yani, Ahmad; Hariyanto, Hariyanto (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2025)
Interfaith marriage is still a controversial issue in Indonesia, legally, socially, and religiously. Article 2, paragraph (1) of the 1974 Marriage Law is the basis for its validity, but its practice gives rise to different interpretations. SEMA No. 2 of 2023 and the Constitutional Court's decision are the latest references. This study aims to analyze the legal settlement of interfaith marriage based on SEMA 2023, examine it from the perspective of Islamic legal sociology, and offer solutions based on Maqashid Syariah. The method used is qualitative with a normative and sociological approach. The primary data sources were obtained from literature studies, including laws, court decisions, scientific journals, as well as various Islamic law and maqashid sharia literature. Data analysis was conducted both descriptively and analytically, employing a legal hermeneutics approach to understand the dynamics of interfaith marriage regulations in Indonesia. This study shows that the absence of clear rules on interfaith marriages has given rise to various interpretations and encouraged alternative practices such as marriage abroad or pseudo-conversion (fraus legis). From the perspective of the sociology of Islamic law, this practice has caused social tension in society. The Maqashid Syariah approach emphasizes the protection of religion, lineage, and human rights. This study concludes the need for more adaptive and inclusive legal reform, considering social justice and humanitarian values, in line with the principles of maqashid syariah.